Hi
The first term is x and the second term is y
Therefore the third term is x+y [1st+2nd], and the fourth is y+(x+y) [2nd+3rd]
What is the 5th term ?
Would appreciate any help with the following question as I do not know where to start.
7, -2, 5, 3, 8
In the sequence above, each term after the first two terms is the sum of the previous two terms.
For example: 3rd term = 5 = 7 +(-2)
(a) A sequence follows the above rule.
The first term is x and the second term is y
The fifth term is 5.
X, y, -, -, 5
Show that 2x+3y=5
(b) Using the same x and y, another sequence follows the above rule.
The first term is y and the second term is x.
The sixth term is 17.
Y, x, -, -, -, 17.
Write down another equation in x and y.
© Find the values of x and y.
1st term = x
2nd term = y
Each term after the first two terms is the sum of the previous two terms
Therefore
3rd term = 1st term + 2nd term = x+y
4th term = 2nd term + 3rd term = y + (x+y) = x + 2y
5th term = 3rd term + 4th term = (x+y) + (x+2y) = 2x + 3y